Pendobrakan Stereotip Perempuan di Iklan Nike dalam Perspektif Dekonstruksi Derrida - Putri, Nur'Aini Rahmawati; Pandrianto, Nigar (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2023)
The presence of women in advertisements is often portrayed as objects through women's stereotypes. Stereotypes of women arerelated to beauty standards that experience construction in people's lives. The use of advertising as a form of mass media conveysmessages with ease in accessing the realities of social life. The development of advertisements with creative ideas shows stereotypes of women by being bolder in changing stereotypes circulating in society through the concept of femvertising. This study uses a qualitative approach by digging deeper into how the Nike Dream Crazier advertisement deconstructs stereotypes ofwomen in society. The researcher uses Jacques Derrida's deconstruction method to find hidden meanings. The subject of this research is the Dream Crazier version of the Nike advertisement video while the research object is the stereotype of women inadvertisements. The results of this study show that the Nike Dream Crazier advertisement provides a picture of deconstructing stereotypes of women through transitions breaking stereotypes of women as strong and daring to break stereotype boundaries. Thedeconstruction of women's stereotypes results from the construction of society in a sustainable manner. Kehadiran perempuan dalam iklan kerap kali digambarkan sebagai objek melalui stereotip perempuan. Stereotip perempuan berkaitan dengan standar kecantikan yang mengalami konstruksi di kehidupan masyarakat. Penggunaan iklan sebagai bentukmedia massa menyampaikan pesan dengan kemudahan dalam mengakses realitas kehidupan sosial. Berkembangnya iklan dengan ide kreatif menunjukkan stereotip perempuan dengan cara lebih berani untuk mengubah stereotip yang beredar di masyarakatmelalui konsep femvertising. Penelitian ini menggunakan pendekatan kualitatif dengan menggali lebih dalam bagaimana iklan Nike Dream Crazier melakukan dekonstruksi dalam stereotip perempuan di masyarakat. Peneliti menggunakan metodedekonstruksi Jacques Derrida untuk menemukan makna-makna tersembunyi. Subjek penelitian ini adalah video iklan Nike versiDream Crazier sedangkan objek penelitian yaitu stereotip perempuan dalam iklan. Hasil penelitian ini memperlihatkan iklan NikeDream Crazier memberikan gambaran dekonstruksi stereotip perempuan melalui transisi mematahkan stereotip perempuansebagai sosok yang kuat dan berani untuk menembus batas-batas stereotip. Dekonstruksi stereotip perempuan diakibatkan olehkonstruksi dari masyarakat secara berkelanjutan.